Bretons, Basques, and Inuit in Labrador and northern Newfoundland: The control of maritime resources in the 16th and 17th centuries - Pope, Peter (Études/Inuit/Studies, 2015)
Early Euro-Inuit contacts in Atlantic Canada raise a complex issue in the ethnohistory of resource exploitation. In the 16th century, Breton, Norman, and Basque crews developed a seasonal salt-cod fishery on the coasts of northern Newfoundland and southern Labrador, in about the same period that the Inuit moved southwards along the Labrador coast. The Basques also exploited the Strait of Belle Isle, between Newfoundland and Labrador, for shore-based whaling. Sometime before 1620, Europeans then appear to have withdrawn from Labrador until about 1680, when Canadian merchants based in Quebec began to exploit the Strait for salmon and seals, while French migratory crews edged northwards again from Newfoundland. European withdrawal from Labrador largely coincided with a long-running guerrilla war, waged by the Inuit against Breton and Basque fishermen exploiting Newfoundland’s Great Northern Peninsula. The chronological coincidence suggests that the movement of Inuit into southern Labrador by the end of the 16th century may well have motivated Europeans to avoid this coast through much of the 17th century. French attitudes to the Labrador Inuit can be contextualized by comparison with contemporary understandings of Euro-Inuit relations elsewhere. Inuit attitudes to Europeans are harder to assess but recognition of their struggle for access to resources is a step towards an appreciation of historical Inuit agency.